Impression Management Strategy Through Emotional Expression of 2024 Presidential Candidates on the KPU RI YouTube Channel - Neysa Muardi; Inri Inggrit Indrayani; Astri Yogatama (Scriptura, 2025)
This research aims to analyze the impression management strategies of the three 2024 Presidential Candidates in the third Presidential debate as seen from nonverbal language, namely microexpressions (facial expressions) and gestures. The third debate held by the Indonesian KPU was held on January 7, 2024. The third debate raised the topics of protection, international relations, security, foreign policy, geopolitics, and globalization. The Presidential Candidate Debate aims to make it easier for the public to understand the vision, mission, and work program of each Presidential Candidate. Therefore, it is necessary to analyze the impression conveyed and the nonverbal language used by each candidate in front of the public to build a positive image. This research uses quantitative descriptive content analysis. Measurements regarding impression management strategies are carried out by looking at emotional behavior (Johnson et al., 2016), gestures (Eunson, 2015), microexpressions (Dubey & Singh, 2019), gestures, and microexpressions of pride and interest (Sauter, 2017) Regarding the data results, this research has eliminated strategies for implementing impression management. This research found that the three 2024 Presidential Candidates in the third debate showed the most ingratiation impression management strategy which was also paired with other strategies such as Anies Baswedan showing ingratiation – self-promotion, Prabowo Subianto showing ingratiation – intimidation, and Ganjar Pranowo showing ingratiation – exemplification.